SCREENING OF Eugenia uniflora (L.) LEAVES IN VARIOUS SOLVENTS FOR QUALITATIVE PHYTOCHEMICAL CONSTITUENTS. - GEEDHU DANIEL,; S.KRISHNAKUMARI, (International Journal of Pharma and Bio Sciences, 2015)
In the last few years there has been an exponential growth in the field of herbal medicine and these drugs are gaining popularity both in developing and developed countries because of their natural origin and less side effects. The current study focuses on qualitative phytochemical screening of primary and secondary metabolites in Eugenia uniflora leaves with different solvents like methanol, ethanol, chloroform, petroleum ether, ethyl acetate, acetone, aqueous cold and hot extracts. Primary metabolites like carbohydrates, proteins, amino acids and secondary metabolites like alkaloids , flavonoids, saponins, tanins , phenols, fattyacids, anthraquione, acids, terpenoids, triterpenoids, sterols, cardiac glycosides, coumarins, carbohydrates, protein, resins, gum & mucilages, phlobtanins, quinones, oxalate, anthocyanin, anthracenoids, emodins, chalcones, anthocyanosides and volatile oils were screened successfully using standard methods. The results obtained in the present study indicates Eugenia uniflora leaves have the potential to act as a source of useful drugs because of the presence of various primary and secondary metabolites .The results are very much encouraging but scientific validation is necessary before being put into practice.